Desain Personal Branding Digital: Membangun Citra Diri Dan Peluang Karier Di Era Digital - Jum Dapi Okta; Yuli Ermawati; Fetty Zulyanti; Ananda Warahmah; Lidya Pratiwi; Yelisa Meifradela; Adi Syahri Ramadhan (Rumah Jurnal PT Citra Air Nusantara, 2026)
Kegiatan seminar bertema